Metodología para el control de gestión en la empresa Decorcasa Cia. Ltda, ciudad de Manta - Ávila Intriago, Josenka Mabel (2019)
The objective of this work was to structure a methodology for management control in the company DECORCASA CIA, LTDA. from Manta city, as a way of aligning its results with the strategic objectives set. This requires a descriptive and exploratory, bibliographic and field investigation, which must obtain the necessary information for the development of the proposal. The investigation procedure was deployed in three stages where a diagnosis of the current state of management control in the company under study was initially made. A set of techniques and tools are applied, such as the interview with the manager of the company, a survey of the workers of the company, an observation sheet for the collection of important data for the study. The specialized literature review was processed to define the methodology that fits DECORCASA's particularities. For the structuring of the system of indicators from the four perspectives of the Balanced Scorecard, it was necessary to develop the Delphi method with the participation of a team of previously selected experts. Finally, the visual control mechanism was established using the traffic light technique, analyzing the results obtained in the period January-June 2019, determining the gaps between the actual and planned values of the indicators established in the financial perspectives, internal processes, clients and learning and growth, which is important for the timely and objective decision making of company executives.